Information Literacy Articles in Science Pedagogy Journals - Cara Bradley (Evidence Based Library and Information Practice, 2013)
Objective – This study sought to determine the extent to which articles about information literacy-related topics have been published in science pedagogy journals. It also explored the nature of these references, in terms of authorship, Association of College and Research Libraries (ACRL) information literacy competency standards addressed, and degree of emphasis on information literacy topics. In addition to characterizing information literacy in the science pedagogy literature, the study presents a methodology that can be adopted by future efforts to explore representations of information literacy in the literature of additional academic disciplines.